O impacto dos formatos de coworking no comportamento das pessoas nas suas relações no ambiente de trabalho - Gomes, Gisela Schulzinger Martino (2021)
The political, economic and social transformations that began at the end of the 20th century, resulting from the advancement of technology and the internet, had a significant impact on people's behavior. For this reason, they have influenced bond and relationship forms among people, as well as practices, professional activities, and work arrangements. One of the consequences was the emergence of a new physical workspace configuration: coworking. In coworking, the physical workspace and infrastructure and office services, are shared by independent professionals from different areas of activity, such as entrepreneurs, selfemployed professionals or freelancers, as well as small companies or specific areas from large corporations. They use the same physical space for work activities, share information and knowledge, thus enriching networks and transforming the place into a dynamic environment for co-creation, exchange of ideas, and learning. Considering the growth of this work model in Brazil and worldwide, this study proposes as a research to understand the impact of coworking on people's behavior and relationships in the work environment. Another aim was to investigate how this model affects conventional working models, as well as the tangible and intangible aspects that guide and motivate decisions to choose and adopt this format. The methodology used was a qualitative approach for deeper understanding of coworking space functioning and different groups of frequent users’ activities. An exploratory research of the literature and secondary data from newspapers, articles, academic journals, publications and social networks were also used.